A Case Study on Competitiveness of the Cinema Exhibition Industry in Malaysia using Porter’s Diamond Framework - Syed Omar, Sharifah Anisah (2007)
Datuk Seri Utama Dr. Rais Yatim the Minister of Culture, Arts and Heritage: “Films are not just a form of entertainment, but they are also a reflection of a nation’s culture and nationality. In fact Arts and in this case film, can cut across political barriers and build better relationship between nations regardless of ideology, beliefs and status.” The cinema exhibition industry underwent substantial growth within the past five years with cinema takings increasing from about RM171 million in 2003 to RM254 million in 2006. This section of the entertainment industry had previously been plagued with piracy that almost completely wiped it out. Although there is still some level of piracy of motion pictures in this country, the reduction has been substantial enough to allow it to now undergo a revival period. This case study assesses the factors which impacts upon this industry’s competitiveness using the analytical framework developed by Michael Porter called Porter’s Diamond. It is believed that the result of this case study provides groundwork and indicators of factors that are currently driving the industry and factors which require strengthening in order to ensure that current levels of growth and competitiveness is sustained